The Role of Immunization Programs in Measles Control: A Public Health Literature Review - Sari, Kartika; Kuntina, Alwansyah; Khatimah, Husnul; Sudirman, Sudirman; Yani , Ahmad (Green Publisher Indonesia, 2026)
Measles is an infectious disease that remains a public health problem, despite the availability of an effective and safe vaccine. Successful measles control depends heavily on the optimal and sustainable implementation of immunization programs. However, measles and measles-rubella (MR) immunization coverage in various regions still faces various challenges, both from an individual and family perspective, as well as from the health care system. This study aims to examine the role of immunization programs in measles control through a public health literature review approach. Using the Systematic Literature Review (SLR) method with the PRISMA approach, secondary data were obtained from primary research articles published between 2021 and 2026 from Google Scholar, PubMed, and ScienceDirect. Of the screened articles, 15 journals met the inclusion criteria. Research findings indicate that the success of immunization programs in controlling measles is influenced by the active role of health cadres, the support and participation of mothers and families, the involvement of health workers, and the quality of management and access to immunization services. Furthermore, several studies have highlighted challenges in immunization implementation, such as limited infrastructure and the impact of the COVID-19 pandemic, which have contributed to declining immunization coverage. The conclusion of this study indicates that measles control requires a comprehensive and integrated approach through strengthening the role of cadres, increasing community literacy, and optimizing the immunization service system. These efforts are expected to increase measles and MR immunization coverage and prevent measles outbreaks in the community